CD25bright NK cells display superior function and metabolic activity under regulatory T cell-mediated suppression. (31st December 2023) - Chen, Ziqing; Tong, Le; Neo, Shi Yong; Li, Shuijie; Gao, Jiwei; Schlisio, Susanne; Lundqvist, Andreas
ABSTRACT: Infusion of natural killer (NK) cells is an attractive therapeutic modality in patients with cancer. However, the activity of NK cells is regulated by several mechanisms operating within solid tumors. Regulatory T (Treg) cells suppress NK cell activity through various mechanisms including deprivation of IL-2 via the IL-2 receptor alpha (CD25). Here, we investigate CD25 expression on NK cells to confer persistence in Treg cells containing solid tumor models of renal cell carcinoma (RCC). Compared with IL-2, stimulation with IL-15 increases the expression of CD25 resulting in enhanced response to IL-2 as evidenced by increased phosphorylation of STAT5. Compared with CD25 dim NK cells, CD25 bright NK cells isolated from IL-15 primed NK cells display increased proliferative and metabolic activity as well as increased ability to persist in Treg cells containing RCC tumor spheroids. These results support strategies to enrich for or selectively expand CD25 bright NK cells for adoptive cellular therapy of NK cells.